Pengembangan Media Pembelajaran Berbasis Literasi Sains Berbantuan Google Sites pada Materi Sumber Energi - Habibah, Ni'mah Nur; Amarulloh, Reza Ruhbani; Suartini, Kinkin (Jurnal Pendidikan dan Ilmu Fisika, 2025)
This study focuses on developing scientific literacy-based learning media using Google Sites for energy source material of energy sources assisted by Google Sites focuses on the feasibility of the media and improving students' scientific literacy skills. The research and development design used in this study is 4D (Define, Design, Develop, and Disseminate) and is limited to the Develop stage. Based on the media expert validation test, an average value of 4.31 was obtained with a very good category. The results of improving students' scientific literacy have an N-gain score of 0.3 (moderate category), as well as positive responses from students after using the learning media. Thus, it can be seen that the learning media based on scientific literacy assisted by Google Sites that have been developed are feasible and have received positive responses from students. The development of this media provides a practical contribution by providing alternative media that can be used by teachers to train students' scientific literacy skills.